Gender differences in mathematics anxiety among elementary school students: a rasch model approach - Yuda Syahputra; Lira Erwinda (Jurnal Konseling dan Pendidikan, 2026)
Mathematics anxiety is an important psychological issue that may negatively affect students' experiences during mathematics learning. This study aimed to examine gender differences in mathematics anxiety among elementary school students. A quantitative comparative design was employed involving 101 students from SDN 25 Air Tawar Selatan, Indonesia, using a total sampling technique. Data were collected using the Mathematics Anxiety Scale and analyzed using the Rasch model to obtain interval-level person measures, followed by Welch's t-test to compare mathematics anxiety between male and female students. The results indicated a statistically significant gender difference in mathematics anxiety, with male students reporting higher levels of mathematics anxiety than female students (p < .001). These findings indicate that gender differences in mathematics anxiety were evident within the study sample. However, because this study employed a cross-sectional comparative design and examined only gender, the findings should be interpreted within the scope of the study and should not be considered evidence of causal relationships. The findings underscore the importance of fostering supportive mathematics learning environments and provide a basis for future studies involving more diverse educational settings and additional psychological and contextual factors.